2019
DOI: 10.5455/ajrms.20190512094558
|View full text |Cite
|
Sign up to set email alerts
|

Marked differences in redox status of professional soccer players depending on training types

Abstract: Objective: An intense physical activity cause inflammation and produces oxidizing molecules that physiologically "train" the body to restoring the homeostatic balance. It's alteration can lead to a sub-clinical pro-inflammatory state known as "oxinflammation." The aim of this study was to measure some inflammation and redox biomarkers in a team of soccer players during a competitive season to identify relationships between oxinflammation, nutrition, workloads, and athletic performances. Methods: Thirty four pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…On the other hand, selenium is related to endogenous antioxidant capacity , and a decrease in Selenium concentration between the two periods was observed. After analyzing our results, we observed that the ACTH value increased in the second measurement in January with respect to the October measurement, and this was in agreement with the evolution described by Bolner et al in 2019. It is unclear whether the protocol studied decreases muscle damage after training and matches, as although a decrease in AA/DHA and AA/EPA ratios was observed, these were not significant. EPA acts competitively against AA for the cyclooxygenase and lipoxygenase enzymes, which are key to reducing inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, selenium is related to endogenous antioxidant capacity , and a decrease in Selenium concentration between the two periods was observed. After analyzing our results, we observed that the ACTH value increased in the second measurement in January with respect to the October measurement, and this was in agreement with the evolution described by Bolner et al in 2019. It is unclear whether the protocol studied decreases muscle damage after training and matches, as although a decrease in AA/DHA and AA/EPA ratios was observed, these were not significant. EPA acts competitively against AA for the cyclooxygenase and lipoxygenase enzymes, which are key to reducing inflammation.…”
Section: Discussionsupporting
confidence: 89%